PERFORMANCE COMPARISON BETWEEN WIND TURBINE AND DIESEL FOR OFF-GRID ELECTRICITY GENERATION IN KANO-NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Grid electricity supply in Nigeria is inadequate and epileptic. Households and businesses use generators for electricity provision with wide-ranging negative impacts on the economy and environment. Wind as a renewable energy is an option to the use of generators in electricity generation.  This study aims to compare the performance of an improved design wind turbine against a conventional wind turbine and a diesel generator for off-grid electricity generation in Kano, Nigeria. The annual energy production, levelized cost of electricity (LCOE) and net present value (NPV) were used for making comparison over a 20-year common life span for Polaris P10-20 turbine, PLEB turbine and a 20kW rated diesel generator. Diesel generator produced highest annual energy output of 61,320kWh against 22,145kWh and 24,159kWh for Polaris and PLEB turbines respectively. The diesel generator had least LCOE of $0.14/kWh against $0.37/kWh and $0.27/kWh for Polaris and PLEB turbines respectively. The NPV of diesel generator is $91,611 negative with no internal rate of return (IRR). It had $90,000 negative cashflow and no payback. The Polaris turbine had negative NPV of $21,386, IRR of 5.03% and could not payback its investment. PLEB turbine had positive NPV of $10,838, IRR of 12.08% and payback period of 12 years. The study has shown that with right investment and environmental policies, deployment of wind turbines for electricity generation in Kano is viable.
Keywords: Diesel versus wind, Electricity generation in Kano, LCOE and NPV, Wind turbine investment, Annual energy production